2023
DOI: 10.3390/nu15071603
|View full text |Cite
|
Sign up to set email alerts
|

Low Self-Esteem and Life Satisfaction as a Significant Risk Factor for Eating Disorders among Adolescents

Abstract: Background: Eating disorders are a problem that is becoming more and more common among younger and younger age groups. Many studies examine the risk factors for EDs, however, the treatment of these diseases is very complicated and requires dietary, psychological and medical intervention. Methods: 233 primary and secondary school students aged 12 to 19 were surveyed using the EAT-26 (Eating Attitudes Test-26) questionnaire, the self-esteem Scale SES and the Cantril scale for life satisfaction. Results: Women, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This is supported by the finding that binge eating symptomatology was associated with a lower level of self-esteem (Cella et al, 2021). However, some studies have found that students with high self-esteem are less likely to suffer from eating disorders, including binge eating (Pelc et al, 2023). It is important to note that the relationship between selfesteem and binge eating is complex and may depend on various factors.…”
Section: Binge Eating Behavior With Emotion Regulationmentioning
confidence: 92%
“…This is supported by the finding that binge eating symptomatology was associated with a lower level of self-esteem (Cella et al, 2021). However, some studies have found that students with high self-esteem are less likely to suffer from eating disorders, including binge eating (Pelc et al, 2023). It is important to note that the relationship between selfesteem and binge eating is complex and may depend on various factors.…”
Section: Binge Eating Behavior With Emotion Regulationmentioning
confidence: 92%
“…A high prevalence of ED was also found in university students [ 21 , 22 ]. In the international context, some studies have reported a higher prevalence of ED in female adolescents [ 23 , 24 , 25 ], while other research has reported no differences of ED between sexes [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…ody esteem, self-esteem, and sexual satisfaction are factors affecting people's well-being (Paradise & Kernis, 2002;Olenik-Shemesh et al, 2018;Vasconcelos et al, 2022) and their low level contributes to reduced satisfaction with life (Vasconcelos et al, 2022;Pelc et al, 2023). However, body esteem, self-esteem, and sexual satisfaction are related (Castellini et al, 2017;Claudat & Warren, 2014;Taleporos & McCabe, 2002), so it is important to look for psychological factors that may contribute to their parallel improvement.…”
mentioning
confidence: 99%